Identification of the dominant hydrogeochemical processes and characterization of potential contaminants in groundwater in Qingyuan, China, by multivariate statistical analysis. Issue 58 (26th September 2018) - Liang, Zuobing; Chen, Jianyao; Jiang, Tao; Li, Kun; Gao, Lei; Wang, Zhuowei; Li, Shaoheng; Xie, Zhenglan
Abstract : In karst areas, groundwater is an important water source for drinking and irrigation purposes; however, karst aquifers are vulnerable and recovery from damage is difficult. Abstract : In karst areas, groundwater is an important water source for drinking and irrigation purposes; however, karst aquifers are vulnerable and recovery from damage is difficult. We collected surface water (pond and river water) and groundwater (hand-pump well, dug well, and borehole water) samples in Qingyuan city, China, to determine the major chemicals in the water with the primary goals of evaluating the geochemical composition, identifying the geochemical processes governing the water chemistry, and identifying the probable sources of potential contaminants in shallow and deep groundwater in the study area. The results revealed marked differences in water chemistry between shallow and deep groundwater. The groundwater composition was largely controlled by rock–water interactions, particularly the dissolution of evaporite minerals ( e.g., calcite, gypsum, and anhydrite), and ion exchange processes were important drivers of the chemical compositions of groundwater in the study area. Moreover, in shallow and deep groundwater, Mg 2+ and SO4 2− concentrations were increased due to the long residence time of deep groundwater, while K + and Na + concentrations were decreased due to anthropogenic input. Finally, factor analysis of the major and trace elements differentiated between anthropogenic and geogenic sources of potential contaminants in karst aquifers.